An air curtain surrounding the solar tower receiver for effective reduction of convective heat loss. (August 2021) - Wang, Qiliang; Yao, Yao; Hu, Mingke; Cao, Jingyu; Qiu, Yu; Yang, Hongxing
Highlights: A novel tower receiver with an air curtain was proposed and designed. A numerical model based on the finite volume method was built and validated. Optimum operating strategy and configurations of air nozzles were investigated. Total heat loss is effectively reduced by 9.60 %. Thermal efficiency is significantly enhanced by 0.49 %. Abstract: External-type solar tower receiver, mounted on the top of a tower with an elevation of dozens or even hundreds of meters, is faced with unavoidably massive convective heat loss due to high operating temperature and high-speed wind at high altitude. To effectively reduce the convective heat loss, a novel solar tower receiver with an air curtain is proposed and designed. In this study, the comprehensive thermal performance of plant-scale tower receivers is numerically studied based on the finite volume method. The impacts of different configurations of air nozzles on the thermal performance of the solar tower receiver are investigated. Furthermore, techno-economic analyses on the Solar Two power plant are also carried out. The results show that, in scenario of incoming wind speed of 15 m/s, the air curtain exerts the best roles at the air-jet angle of 45°, a distance of 1.50 m from the receiver surface, and air-jet velocity of 16 m/s in an operating mode of switching off the air nozzles at the windward and leeward sides. Compared with the original receiver, the heat loss of the proposed receiver is effectively reduced by 9.60 %, and the efficiency and electricity power production are enhanced by approximately 0.49 %.